Risk Analysis of Mount Ijen Eruption Disaster Based on Geographic Information Systems - Khairul Anwar; Isa Ma'rufi; Ristya Widi Endah Yani (Humanistic Network for Science and Technology (HNST), 2018)
Mount Ijen is a strato active volcano located in Banyuwangi and Bondowoso Regencies. Mount Ijen has a risk that can cause various problems, both related to social, economic and public health issues. The aim of this study is to analyze the risk of the disaster of the Mount Ijen eruption and develop a map of disaster-prone risks. This type of research was quantitative descriptive research. The results showed that the four sub-districts of Mount Ijen threat level included in the category of KRB II (medium), the capacity level was included in the medium category and the level of vulnerability was different for each sub-category of high vulnerability categories were Wongsorejo and Licin Districts. The conclusion of the risks of the Mount Ijen eruption based on the GIS map of Licin Subdistrict and Wongsorejo Subdistrict are categorized as high risk, Kalipuro Subdistrict is included as the medium risk category and Ijen Subdistrict as the low risk category. Keywords: Risk Analysis, GIS, Mount Ijen, Disaster